Peluang dan tantangan aplikasi baut tulang mampu terdegradasi berbasis logam magnesium - Hermanto, A.; Burhanudin, Y.; Sukmana, I. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2016)
This paper reviews the potential and challenges for the application of biodegradable bone screw materials. Currently, in the field of medical sciences and biomedical engineering devices, a non-degradable bone screw is the most acceptable concept to repair a bone fracture. However, with the new intervention and development of advanced materials, either in polymer-based or metallic-based, opens a possibility to use a degradable bone screw. Magnesium-based material is one of the most promising candidates for biodegradable bone screw application, which is the main focus of this paper. Casting technologies for producing magnesium alloys will also highlighted.